Anacyclus pyrethrum enhances fertility in cadmium-intoxicated male rats by improving sperm functions - Aya A. Mahmoud; Mennat Allah M. Shaaban; Wesam T. Basal (BMC, 2024)
Abstract Background Environmental pollutants, particularly heavy metals, have been frequently connected to male infertility. Cadmium was previously shown to reduce male fertility by causing oxidative stress. Anacyclus pyrethrum is a well-known medicinal plant. Most of its parts, notably the roots, have excellent antioxidant and anti-inflammatory properties. The present study investigated the potential ability of Anacyclus pyrethrum to protect male rats against cadmium reproductive toxicity. Methods Twenty-eight adult Wistar male rats (8 weeks old) weighing (170-200g) were randomly divided into four groups (n = 7): group (1) the control, group (2) was orally administrated with Anacyclus pyrethrum extract (100mg/kg) for 56 consecutive days, group (3) received a single intraperitoneal (IP) injection of cadmium chloride (1mg/kg), and group (4) received a single IP dose of CdCl2 followed by 8 weeks of oral Anacyclus extract treatment. Results Cadmium Cd toxicity resulted in a significant decrease in the concentration of antioxidant enzymes (superoxide dismutase SOD and glutathione peroxidase GPx) in the semen coupled with a significant rise in malondialdehyde MDA level. Consequently, sperm analysis parameters were significantly affected showing decreased motility, viability, concentration and increased morphological aberrations. DNA fragmentation was also detected in the sperms of rats exposed to Cd using comet assay. Serum levels of testosterone T, follicle stimulating hormone FSH, and luteinizing hormone LH were significantly decreased. The mRNA expression levels of sex hormone receptors (FSHR, LHR and AR) in the testis of the Cd exposed rats were significantly decreased. Expression levels of Bax and Bcl2 genes in the sperms of Cd intoxicated rats were also affected shifting the Bax/Bcl2 ratio towards the induction of apoptosis. Co-treatment with the Anacyclus pyrethrum extract restored the oxidative enzymes activities and decreased the formation of lipid peroxidation byproduct, which in turn ameliorated the effect of Cd on sperm parameters, sperm DNA damage, circulating hormone levels, gene expression and apoptosis. These results indicate that Anacyclus pyrethrum could serve as a protective agent against cadmium-induced sperm toxicity. Conclusion Taken together, it can be concluded that the antioxidant activities of Anacyclus pyrethrum restored the semen quality and enhanced fertility in Cd-intoxicated male rats.